Pengaruh Pemberian Variasi Media Pakan terhadap Produksi Berat Segar Maggot (Hermetia illucens) - Faiza, Nurul; Ma'ruf, Muhammad Muizzul; Saiku Rokhim (Biosel Biology Science and Education, 2026)
Hermetia illucens (Black Soldier Fly/BSF) is an insect capable of reducing organic waste through its larvae that consume various waste and produce biomass rich in protein and fat. Therefore, the quality of the feed media especially its protein content significantly influences the growth of these larvae. This study aims to identify the effect of variations in feed media on the fresh weight of BSF maggots to increase production efficiency as an alternative protein source. The study design used a Completely Randomized Design (CRD) with 27 experimental units replicated nine times. Six-day-old BSF larvae were reared for 14 days under controlled environmental conditions. Three types of feed media were used: tofu dregs, corn dregs, and vegetable waste. The results showed that the feed media significantly influenced the fresh weight of larvae, where the P3 (tofu dregs) treatment produced the highest weight of 23.5 grams, much higher than P1 (11.3 grams) and P2 (10.6 grams). The superiority of P3 is thought to originate from the nutritional content of tofu dregs, especially its higher crude protein, thus better supporting larval growth. Thus, selecting the right feed media is an important factor in increasing the efficiency of BSF maggot production as an alternative protein source. Keywords: Black Soldier Fly, Feed Media, Maggot Fresh Weight, Larvae Growth